Pengaruh penambahan tepung kulit bawang terhadap kecernaan protein kasar pakan, pertambahan bobot badan dan persentase karkas itik Mojosari - Yoseph Avian Saputra; Istna Mangisah; Bambang Sukamto (Faculty of Animal Science, Universitas Brawijaya, 2016)
This study aimed to determine the effect of addition of onion skin flour (OSF) and garlic skin flour (GSF) on feed digestibility of crude protein, body weight gain and carcass percentage of Mojosari ducks. The research used 168 Mojosari duck males aged 4 weeks and had an average weight of 335.5 ± 72 g/duck (CV = 7.8%). The study used completely randomized design with7 treatments and 4 replications (T0 = basal feed (BF); T1 = BF + 3% OSF; T2 = BF+ 6% OSF; T3 = BF+ 3% GSF; T4 = BF+ 6% GSF; T5 = BF + 1.5% OSF + 1.5% GSF; and T6 = BF+ 3% OSF + 3% GSF).The results showed that the protein digestibility was found higher (P <0.05) in T6 (80.08%) than T0 (74.76%), T1 (73.71%), and T2 (75.54%). Meanwhile, protein digestibility of T4 (79.26%) were higher (P <0.05) than T1 (73.71%). Another findings showed that body weight gain of T0 (15,88 g) were lower (P <0.05) than T1 (18.48 g); T2 (18.42 g); T3 (17.96 g); T4 (19.77 g); and T6 (19.05 g). The addition of OSF and GSF could not influence (P>0.05) the duck carcass percentage. The study concluded that the addition of 6% GSF and combination of 3% OSF + 3% GSF could improve crude protein digestibility and weight gain, but was not able to increase the percentage of duck carcasses. Keywords: duck, digestible protein, body weight, carcas